Simulation study comparing exposure matching with regression adjustment in an observational safety setting with group sequential monitoring. (15th December 2014) - Stratton, Kelly G.; Cook, Andrea J.; Jackson, Lisa A.; Nelson, Jennifer C.
<x xml:space="preserve">Abstract</x> Sequential methods are well established for randomized clinical trials (RCTs), and their use in observational settings has increased with the development of national vaccine and drug safety surveillance systems that monitor large healthcare databases. Observational safety monitoring requires that sequential testing methods be better equipped to incorporate confounder adjustment and accommodate rare adverse events. New methods designed specifically for observational surveillance include a group sequential likelihood ratio test that uses exposure matching and generalized estimating equations approach that involves regression adjustment. However, little is known about the statistical performance of these methods or how they compare to RCT methods in both observational and rare outcome settings. We conducted a simulation study to determine the type I error, power and time‐to‐surveillance‐end of group sequential likelihood ratio test, generalized estimating equations and RCT methods that construct group sequential Lan–DeMets boundaries using data from a matched (group sequential Lan–DeMets‐matching) or unmatched regression (group sequential Lan–DeMets‐regression) setting. We also compared the methods using data from a multisite vaccine safety study. All methods had acceptable type I error, but regression methods were more powerful, faster at detecting true safety signals and less prone to implementation difficulties with rare events than exposure matching methods. Method performance also depended on the distribution of information and extent of confounding by site. Our results suggest that choice of sequential method, especially the confounder control strategy, is critical in rare event observational settings. These findings provide guidance for choosing methods in this context and, in particular, suggest caution when conducting exposure matching. Copyright © 2014 John Wiley & Sons, Ltd.